Vellozioid roots allow for habitat specialization among rock‐ and soil‐dwelling Velloziaceae in campos rupestres. (14th December 2019) - Abrahão, Anna; de Britto Costa, Patricia; Teodoro, Grazielle S.; Lambers, Hans; Nascimento, Diego L.; Adrián López de Andrade, Sara; Ryan, Megan H.; Silva Oliveira, Rafael
Abstract: Plant growth on harsh substrates (habitat specialization) requires specific traits to cope with stressful conditions. We tested whether traits related to nutrient acquisition (root colonization by fungal symbionts, and plant morphological and physiological specializations), and nutrient use (leaf nitrogen (N) and phosphorus (P) concentrations and N‐ and P‐remobilization efficiency), were related to habitat specialization for 27 species of Velloziaceae growing either in soil or on rocks in extremely P‐impoverished campos rupestres habitats. If habitat specialization were to drive trait sorting, then we expect traits to differ between those substrates. Both soil and rock‐dwelling species presented a very low proportion of root length colonized by arbuscular mycorrhizal and dark‐septate fungi. However, rhizosheaths were only observed in soil‐dwelling species, and vellozioid roots, a specialization that allows for mining P and dissolving quartzite rock, were mostly found in rock‐dwelling species. We did not observe differences in nutrient‐use traits between rock‐ and soil‐dwelling species. Root specializations are strongly correlated with microhabitats, and the presence of vellozioid roots seems to mediate bare rock specialization. There is an overall P limitation of plant productivity both on rock and in soil of campos rupestres, which does not drive the sorting of traits related to above‐ground nutrient use and symbiotic P acquisition. Therefore, nutrient impoverishment is indeed a very strong environmental filter in campos rupestres as a whole, but habitat specialization plays an important role in the spatial distribution of Velloziaceae between contrasting substrates. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Translated Abstract: Resumo O crescimento de plantas sobre substratos considerados estressantes (especialização de habitat) requer atributos específicos das plantas. Nós testamos se os atributos relacionados à aquisição de nutrientes (colonização das raízes por fungos simbióticos, especializações morfológicas e fisiológicas das plantas), e ao uso de nutrientes (concentração foliar de nitrogênio (N) e fósforo (P) e eficiência de remobilização de N e P) estavam relacionados com a especialização de habitat. Nós analisamos os atributos em 27 espécies de Velloziaceae que crescem sobre solo ou rocha em campos rupestres extremamente empobrecidos em P. Se a especialização de habitat fosse responsável pela diferenciação dos atributos, então nós esperaríamos que os atributos diferissem entre esses substratos. Tanto as espécies que crescem sobre solo, quanto as que crescem sobre rocha apresentaram uma proporção muito pequena da raiz colonizada por micorrizas arbusculares e fungos endofíticos melanizados ("dark septate"). No entanto, somente observamos areia aderida às raízes ("rhizosheaths") nas plantas que crescem sobre solo. As raízes velozióides, uma especialização que permite a dissolução da rocha e a subsequente aquisição de P, foram observadas principalmente nas espécies crescendo sobre rochas. Nós não observamos diferenças entre os atributos relacionados ao uso de nutrientes entre espécies crescendo sobre os diferentes tipos de substrato. Especializações radiculares apresentaram forte correlação com o microhabitat, e a presença de raízes velozióides parece mediar a especialização no crescimento sobre a rocha nua. Em campos rupestres, existe uma limitação generalizada do crescimento vegetal pela baixa concentração de P, tanto no solo quanto sobre as rochas, o que não resultou em diferenças nos atributos foliares associados com o uso de N e P. Portanto, a escassez de nutrientes constitui de fato um forte filtro ambiental em campos rupestres como um todo, mas a especialização de habitat tem um papel importante na distribuição de espécies das Velloziaceae em substratos contrastantes. A free Plain Language Summary can be found within the Supporting Information of this article.